Elevated neutrophil‐to‐lymphocyte ratio (NLR) is associated with poorer progression‐free survival in unresectable stage III NSCLC treated with consolidation durvalumab. Issue 21 (16th September 2022) - Nindra, Udit; Shahnam, Adel; Stevens, Samuel; Pal, Abhijit; Nagrial, Adnan; Lee, Jenny; Yip, Po Yee; Adam, Tamiem; Boyer, Michael; Kao, Steven; Bray, Victoria
Abstract: Sustained elevation in neutrophil‐to‐lymphocyte ratio (NLR) after initial chemoradiotherapy (CRT) has been shown to correlate with worse prognosis in a number of solid organ malignancies. Here, we conducted a retrospective observational cohort study involving six sites across Sydney, Australia, including all patients with unresectable stage III NSCLC treated with CRT and consolidation durvalumab between January 2018 and September 2021. Patients had NLR collected prior to CRT and prior to cycle one of durvalumab. We used an NLR value of 3 to stratify patients into high and low groups. Patients with sustained NLR were defined as those with values ≥3 at both timepoints. A total of 145 patients were included in the study. The median age of patients was 66 years with median follow‐up of 15.1 months. The median PFS was 17.6 months in the pre‐CRT NLR high cohort and not reached (NR) in the pre‐CRT NLR low cohort (HR 1.99; p  = 0.01). The median OS was 35.5 months in the high pre‐CRT NLR cohort compared with 42.0 months in the low pre‐CRT NLR cohort (HR 2.62; 95% CI: 1.23–5.56, p  < 0.01). Median PFS for sustained NLR elevation was 17.1 months versus NR (HR 1.5; p  < 0.01). Pre‐CRT NLR and sustained NLR remained independently prognostic for PFS on multivariate analysis ( p  = 0.04, p  = 0.01) respectively. Pre‐CRT NLR and sustained NLR is associated with worse PFS outcomes in unresectable stage III NSCLC treated with CRT and durvalumab. Pre‐CRT NLR is also associated with worse OS. Abstract : Pre‐CRT NLR and sustained NLR is associated with worse PFS outcomes in unresectable stage III NSCLC treated with CRT and durvalumab. The median PFS was 17.6 months in the pre‐CRT NLR high cohort and not reached (NR) in the pre‐CRT NLR low cohort (HR 1.99; p  = 0.01).